2021
DOI: 10.1088/1361-6560/ac35f1
|View full text |Cite
|
Sign up to set email alerts
|

Applications of nanodosimetry in particle therapy planning and beyond

Abstract: This topical review summarizes underlying concepts of nanodosimetry. It describes the development and current status of nanodosimetric detector technology. It also gives an overview of Monte Carlo track structure simulations that can provide nanodosimetric parameters for treatment planning of proton and ion therapy. Classical and modern radiobiological assays that can be used to demonstrate the relationship between the frequency and complexity of DNA lesion clusters and nanodosimetric parameters are reviewed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 276 publications
0
13
0
Order By: Relevance
“…For intensity-modulated proton radiation therapy, composed of several heterogeneous radiation fields and multiple pencil beams, the LET spectrum will be even wider. In particular, the high-LET component will be responsible for elevated radiobiological effects (Rucinski et al 2021). While overall, high-LET is recognized to be correlated with radiographic image changes, there is no consensus on the impact of LET D on this (Bahn et al 2020, Garbacz et al 2021, Niemierko et al 2021.…”
Section: Discussionmentioning
confidence: 99%
“…For intensity-modulated proton radiation therapy, composed of several heterogeneous radiation fields and multiple pencil beams, the LET spectrum will be even wider. In particular, the high-LET component will be responsible for elevated radiobiological effects (Rucinski et al 2021). While overall, high-LET is recognized to be correlated with radiographic image changes, there is no consensus on the impact of LET D on this (Bahn et al 2020, Garbacz et al 2021, Niemierko et al 2021.…”
Section: Discussionmentioning
confidence: 99%
“…It was therefore suggested that measurement of the relevant F normalk (for direct traversals) in the corresponding volume could be used to predict the radiobiological response of the biological system to different radiation qualities, including unknown fields (Conte et al , 2017a; 2018). Further comments by Rabus (2020) and a review by Rucinski et al (2021) include consideration of these and other concepts linking nanodosimetry to radiobiology and to potential applications in particle therapy (PT).…”
Section: Applications Of Stochastic Characteristics Of Radiation Inte...mentioning
confidence: 99%
“… 21 , 22 LET d combines different beam qualities, contributing to damage in a single value, and can be used as a predictor for RBE, 23 considering a suggested LET-RBE linear dependence. 24 , 25 , 26 , 27 To avoid RBE uncertainty while reducing biological variability in treatment planning, metrics based on computable physical parameters (eg, dose and LET-RBE dependence [as a proxy for response]) have been suggested (eg, product between dose and LET d [DLET d ]). 25 , 26 , 28 …”
Section: Introductionmentioning
confidence: 99%